Draft Sixth Five Year Plan (1978-83) Volume I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
This island archipelago of India with its maritime importance is perhaps better known abroad than in the mother country as a whole; but a good deal of knowledgeable information for Plan purposes is interestingly found in the Planning Commission’s own "Yojana" - special issue - Volume XX/13 of 15th August, 1976. of late, the Islands have begun to turn the corner changing direction towards a more meaningful existence, no more to be passed off merely as ideal grounds for lifers, political detenus or displaced families. Indeed, in their quest for their own strategic personality, the Andamans Nicobars have already begun to overtake their erstwhile image of a Black Water Prison.
Andaman and Nicobar Administration, Format and Statistical Statements